Identification and functional analysis of the SARS-COV-2 nucleocapsid protein - Gao, Tianyi; Gao, Yingdong; Liu, Xiangxiang; Nie, Zhenlin; Sun, Huilin; Lin, Kang; Peng, Hongxin; Wang, Shukui (BMC microbiology, 2021)
A severe form of pneumonia, named coronavirus disease 2019 (COVID-19) by the World Health Organization is widespread on the whole world. The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was proved to be the main agent of COVID-19. In the present study, we conducted an in depth analysis of the SARS-COV-2 nucleocapsid to identify potential targets that may allow identification of therapeutic targets. The SARS-COV-2 N protein subcellular localization and physicochemical property was analyzed by PSORT II Prediction and ProtParam tool. Then SOPMA tool and swiss-model was applied to analyze the structure of N protein. Next, the biological function was explored by mass spectrometry analysis and flow cytometry. At last, its potential phosphorylation sites were analyzed by NetPhos3.1 Server and PROVEAN PROTEIN. SARS-COV-2 N protein composed of 419 aa, is a 45.6 kDa positively charged unstable hydrophobic protein. It has 91 and 49% similarity to SARS-CoV and MERS-CoV and is predicted to be predominantly a nuclear protein. It mainly contains random coil (55.13%) of which the tertiary structure was further determined with high reliability (95.76%). Cells transfected with SARS-COV-2 N protein usually show a G1/S phase block company with an increased expression of TUBA1C, TUBB6. At last, our analysis of SARS-COV-2 N protein predicted a total number of 12 phosphorylated sites and 9 potential protein kinases which would significantly affect SARS-COV-2 N protein function. In this study, we report the physicochemical properties, subcellular localization, and biological function of SARS-COV-2 N protein. The 12 phosphorylated sites and 9 potential protein kinase sites in SARS-COV-2 N protein may serve as promising targets for drug discovery and development for of a recombinant virus vaccine.